Power-quality-oriented optimization in multiple three-phase adjustable speed drives - Yang, Y.; Davari, P.; Blaabjerg, F.; Zare, Firuz (2016)
© 2016 IEEE. As an almost standardized configuration, Diode Rectifiers (DRs) and Silicon-Controlled Rectifiers (SCRs) are commonly employed as the front-end topology in three-phase Adjustable Speed Drive (ASD) systems. Features of this ASD configuration include: structural and control simplicity, small volume, low cost, and high reliability during operation. Yet, DRs and SCRs bring harmonic distortions in the mains and thus lowering the overall efficiency. Power quality standards/rules are thus released. For multiple ASD systems, certain harmonics of the total grid current can be mitigated by phase-shifting the currents drawn by SCR-fed drives, and thus it is much flexible to reduce the Total Harmonic Distortion (THD) level in such applications. However, the effectiveness of this harmonic mitigation scheme for multiple ASD systems depends on: a) the number of parallel drives, b) the power levels, and c) the phase-shifts (i.e., firing angles) for the corresponding SCR-fed drives. This paper thus adopts a particle swarm optimization algorithm to optimize the power levels and the firing angles for multi-drive systems considering a fixed number of drives when practically implemented. The optimization is done to minimize the THD level of the total current at the point of common coupling. Simulations with the optimized results are carried out and laboratory tests on a two-drive system are provided to demonstrate the phase-shifting harmonic mitigation scheme. Issues concerning the practical implementation of the optimal results in multi-drive systems are also addressed.